Corporate Leverage Transmission under Information Asymmetry: Evidence from Non-financial Firms of Pakistan - Ahmed, Zeeshan; Saleem, Qasim; Bhatti, Abdul Qadir; Ahmed, Bilal (International Journal of Economics and Financial Issues, 2020)
The study aims to examine the relation between capital structure and information asymmetry. For this purpose, pooled OLS and fixed effect model regression techniques are used for empirical analysis of the study. The annual data has been taken from analysis of Pakistan Stock Exchange listed companies' balance sheet published by State Bank of Pakistan (SBP) from the period of 2006 to 2015.The result depicts a noticeable increase of debt in capital structure as a result of an increase in information asymmetry and it also shows the consistency with pecking order theory. Firm follows the hierarchical patterns of financing and the results are robust against different econometric techniques. The key findings also give some suggestions to increase the tendency of funds raising through debt financing when market has information asymmetry. Keywords: Information asymmetry, Corporate Leverage, Pecking Order Hypothesis JEL Classification: G3 DOI: https://doi.org/10.32479/ijefi.9710